Sustainable Heritage Tourism Development : A Study Systematic Literature Review - Nirmana Aulia Firdausi (Universitas Pendidikan Indonesia, 2024)
Tourism is a multifaceted field with a path of adventure, cultural immersion, and beautiful encounters. Cultural heritage certainly has benefits that can be implemented in today's era. Of course, this article has provided a descriptive analysis based on the worldview of various authors. The main objectives of this study are to determine which indicators should be used in measuring the level of desirability of heritage cities, to see in which countries the most sustainable urban heritage studies are conducted, and to find trends and areas of study related to this research topic. The research used in this study is the SLR (Systematic Literature Review) method. Data collection was carried out by documenting all articles that have similar research in the research report. This study highlights the importance of infrastructure development, community involvement, education and stakeholder collaboration in achieving sustainable tourism heritage. Through initiatives like this, Malaysia can continue to attract tourists while preserving its unique cultural heritage for future generations.